2018
DOI: 10.11648/j.ijaaa.20180402.11
|View full text |Cite
|
Sign up to set email alerts
|

Architecture, Virtual Reality, Spatial Visualization, Learning Styles, and Distance Education

Abstract: What is the next generation of learning technology: the cellphone, your watch, virtual reality, or all of the above.The research question being asked is: How can Virtual Reality (VR) assist students in learning? This research proves that virtual reality technology does enhance 3D spatial visualization skills of students. Due to the nature of their learning styles, many students need to interact with 3D scenes to enhance their spatial visualization skills, to see and understand the 3D model. This research prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…Penelitian ini memberikan hasil berupa pembuktian hipotesis bahwa VR bisa menjadi model yang paling efektif untuk membantu menghadirkan persepsi spasial bagi pelajarnya. Hasil penelitian juga menyatakan bahwa VR dapat menghasilkan visualisasi spasial yang lebih akurat dibanding model fisik/ maket (Duwain Brazley, 2018). Penelitian ketiga merupakan karya dari Chiu Shui Chan yang berjudul Virtual Reality in Architectural Design.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Penelitian ini memberikan hasil berupa pembuktian hipotesis bahwa VR bisa menjadi model yang paling efektif untuk membantu menghadirkan persepsi spasial bagi pelajarnya. Hasil penelitian juga menyatakan bahwa VR dapat menghasilkan visualisasi spasial yang lebih akurat dibanding model fisik/ maket (Duwain Brazley, 2018). Penelitian ketiga merupakan karya dari Chiu Shui Chan yang berjudul Virtual Reality in Architectural Design.…”
Section: Pendahuluanunclassified
“…Penelitian ketiga merupakan karya dari Chiu Shui Chan yang berjudul Virtual Reality in Architectural Design. Penelitian ini menyatakan bahwa VR bisa menjadi salah satu solusi sarana penelitian agar dapat mendapat informasi yang beragam secara virtual (Duwain Brazley, 2018).…”
Section: Pendahuluanunclassified
“…Spatial intelligence involves skills to put mental images into visualization. While, on other hand, bodily kinesthetic refers to the ability to skillfully handle things manually & correct exhibition of body movements (Brazley, 2018a(Brazley, , 2018b. Sitoy et al (2021b) found that incorporating digital literacy into curriculum significantly improved students' linguistic and logical-mathematical intelligences, highlighting the importance of integrating technology in education.…”
Section: Introductionmentioning
confidence: 99%